1999
DOI: 10.1038/sj.ejhg.5200231
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in Rsk-2, the gene for Coffin-Lowry syndrome (CLS)

Abstract: Coffin-Lowry syndrome (CLS) is an X-linked disorder characterized by facial dysmorphism, digit abnormalities and severe psychomotor retardation. CLS had previously been mapped to Xp22.2. Recently, mutations in the ribosomal S6 kinase (Rsk-2) gene were shown to be associated with CLS. We have tested five unrelated individuals with CLS for mutations in nine exons of Rsk-2 using Single Strand Conformation Polymorphism (SSCP) analysis. Two patients had the same missense mutation (C340T), which causes an arginine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Despite these similarities, substantial evidence indicates a functional independence of the individual RSK family members. First, none of the RSKs complements deficient RSK2 in CLS (46) and possibly RSK4 in XLMR (48). Second, while RSK1-3 are activated through ERK, RSKB, as shown by its responses to MAPKs, effects of SB202190 and PD98059, and direct activation in vitro, mainly depended on p38 and to a lesser extent ERK (61,63).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these similarities, substantial evidence indicates a functional independence of the individual RSK family members. First, none of the RSKs complements deficient RSK2 in CLS (46) and possibly RSK4 in XLMR (48). Second, while RSK1-3 are activated through ERK, RSKB, as shown by its responses to MAPKs, effects of SB202190 and PD98059, and direct activation in vitro, mainly depended on p38 and to a lesser extent ERK (61,63).…”
Section: Discussionmentioning
confidence: 99%
“…Intragenic deletions, nonsense and splice-site mutations in the rsk gene mapped to Xp22.2 were shown to be associated with CLS (Coffin-Lowry syndrome) in human, an X-linked disorder characterized by facial dysmorphism, digit abnormalities and severe psychomotor retardation [40,41]. RSK was also found to be an important activator of tumor generation.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, disease causing mutations have been described in the ribosomal protein S6 kinase (RSK2). [4][5][6] A wide range of different types of mutations have been described, distributed throughout the gene, many associated with premature translation termination, and most associated with predicted loss of function of the mutant allele. 6 The application of these findings in clinical practice has served not just to expand the understanding of the mutational basis of the classical syndrome, but has also shown that atypical, mild forms of Coffin-Lowry syndrome exist.…”
mentioning
confidence: 99%
“…7 Despite these occasional clinical surprises, most patients harbouring pathogenic mutations of the RSK2 locus have shown clinical characteristics consistent with those expected in Coffin-Lowry syndrome. 5 However, as established by a recent mutational screen in 250 patients clinically suggestive of Coffin-Lowry syndrome, mutations are found in by no means all such patients. 6 Indeed mutations were not identified in 66% of patients included in the mutation studies.…”
mentioning
confidence: 99%